Preparing an interview schedule for an ethnographic study in the business community - Rajeswary A. Sargunan (Journal of Modern Languages)
The interview that is to be described in this paper was designed as part of a pilot study that was carried out in a multinational manufacturing organization in Malaysia (henceforth referred to as MNMC as they prefer anonymity).The pilot study was in turn part of a larger research project that sought to investigate the gap between effective and non-effective technical reports (according to "local criteriaâ€) produced in MNMC. There would also be further investigation between the locally effective technical report and the generically ideal form for the organization (more on this below).